A weather-resistant metal TPU high and low temperature film and preparation method thereof

Through the composite structure of the PU layer, hot melt adhesive layer and TPU layer, combined with weathering metal powder and nano mica powder regulator, the problem of insufficient flame retardant and water vapor barrier performance of the TPU film is solved, and the weather resistance and height resistance of the product are significantly improved Low temperature performance.

CN118849590BActive Publication Date: 2024-12-27QUANZHOU SIMDA GARMENTS & SHOES MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411343115.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2024-12-27
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

The existing TPU film has poor flame retardant performance and low water vapor barrier performance, making it difficult to achieve coordination between flame retardant and water vapor barrier, as well as insufficient weather resistance and high and low temperature resistance, which limits the efficiency of the product.

Method used

Using a composite structure of the PU layer, hot melt adhesive layer and TPU layer, the PU layer consists of the PU bottom layer, the PU middle layer and the PU surface layer, and bonds with the TPU layer through the hot melt adhesive layer, and adds weather-resistant metal powder and doping to the PU layer. It is used to adjust the cover stabilizer and blend modifier with nano mica powder. Functional aids such as flame retardant and zinc oxide are added to the TPU layer to optimize the layer spacing and structure to improve the flame retardant and water vapor barrier properties.

Benefits of technology

It significantly improves the flame retardant, water vapor barrier coordination, weather resistance, high and low temperature resistance, and enhances the flame retardant and performance stability of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention relates to the technical field of high and low temperature films, and specifically discloses a weather-resistant metal TPU high and low temperature film and a preparation method thereof, including a PU layer, a hot melt adhesive layer and a TPU layer; wherein both sides of the PU layer are bonded and compounded by the hot melt adhesive layer and the TPU layer. The TPU high and low temperature film of the present invention is compounded by a PU layer, a hot melt adhesive layer and a TPU layer, and the TPU layer is made by a TPU film. The TPU film uses TPU resin, a flame retardant, a silane coupling agent KH560, stearic acid, zinc oxide and an antioxidant as functional additives, and a stabilizer and a blending modifier adjusted by mixing nano mica powder are added as a coordinating agent. The two cooperate and work together to enhance the effect. The flame retardant and water vapor barrier coordination effect of the product is significant, and the weather resistance and high and low temperature stability of the product are obvious.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high and low temperature films, and in particular to a weather-resistant metal TPU high and low temperature film and a preparation method thereof. Background Art

[0002] Thermoplastic TPU elastomers are widely used in processing methods such as injection, extrusion, calendering and dissolving into solution-type resins due to their good elasticity, excellent physical properties and good mechanical strength. They are plastic materials frequently used by plastic processing industries. The products made from them cover the range of industrial applications and civilian necessities, such as shoe materials.

[0003] The existing TPU film has poor flame retardancy and low water vapor barrier properties, making it difficult to achieve coordination between flame retardancy and water vapor barrier properties. The product also has poor weather resistance and high and low temperature stability, which limits the product's use efficiency. Summary of the invention

[0004] In view of the defects of the prior art, the purpose of the present invention is to provide a weather-resistant metal TPU high and low temperature film and a preparation method thereof to solve the problems raised in the above background technology.

[0005] The present invention solves the technical problem by adopting the following technical solution:

[0006] The present invention provides a weather-resistant metal TPU high and low temperature film, comprising a PU layer, a hot melt adhesive layer and a TPU layer; wherein both sides of the PU layer are bonded and compounded by the hot melt adhesive layer and the TPU layer;

[0007] The PU layer also includes a PU bottom layer, a PU middle layer and a PU surface layer, and the PU bottom layer, the PU middle layer and the PU surface layer are arranged in sequence from bottom to top;

[0008] The PU bottom layer, PU middle layer and PU surface layer are all made by coating a PU patch on a non-woven fabric base fabric;

[0009] The PU patch is made of the following raw materials in parts by weight:

[0010] 100-110 parts of polyurethane PU glue, 10-15 parts of butanone solvent, 4-7 parts of weather-resistant metal powder, 2-4 parts of silane coupling agent KH560, and 3-6 parts of curing agent;

[0011] The TPU layer is made of a TPU film, and the TPU film includes the following raw materials in parts by weight:

[0012] 45-55 parts of TPU resin, 8-12 parts of stabilizer adjusted by mixing with nano-mica powder, 4-7 parts of flame retardant, 3-6 parts of blending modifier, 3-5 parts of silane coupling agent KH560, 2-5 parts of stearic acid, 2-5 parts of zinc oxide, and 2-4 parts of antioxidant.

[0013] Preferably, the weather-resistant metal powder is made of aluminum powder, silicon dioxide and ferric oxide in a weight ratio of 1:2:1; the curing agent is hexamethylene diisocyanate; the antioxidant is antioxidant 1010; and the flame retardant is magnesium hydroxide.

[0014] Preferably, the thickness of the TPU layer is 0.3-0.5 mm; the thickness of the PU bottom layer, the PU middle layer and the PU surface layer are all 0.1-0.2 mm; the thickness of the hot melt adhesive layer is 0.1-0.2 mm;

[0015] The preparation method of the hot melt adhesive layer is as follows:

[0016] 30-35 parts of polyester polyol with a number average molecular weight of 2000, 35-40 parts of toluene diisocyanate, 2 parts of dibutyltin dilaurate, and 4-7 parts of 1,4-butanediol are mixed, and then extruded in a twin-screw extruder at an extrusion temperature of 165° C. After extrusion, the mixture is cooled to obtain a hot melt adhesive layer;

[0017] The polyester polyol is prepared by mixing sebacic acid, terephthalic acid and ethylene glycol in a weight ratio of 1:2:4, then adding isopropyl zirconate of 5% by weight of the sebacic acid, and heating to 140° C. for polycondensation to obtain the polyester polyol.

[0018] Preferably, the preparation method of the stabilizer mixed with nano-mica powder is:

[0019] S11: heat treating the nano mica powder at 210-230°C for 5-10 min, then heating it to 350°C at a rate of 2-5°C / min, keeping the temperature for 5 min, and finally air cooling it to room temperature to obtain heat-treated nano mica powder;

[0020] S12: immersing the heat-treated nano-mica powder into a sufficient amount of soaking liquid for ultrasonic soaking, filtering and drying after the soaking is completed to obtain soaked nano-mica powder;

[0021] The leaching solution is prepared by mixing a sodium silicate solution having a mass fraction of 2-5%, a phosphate buffer solution having a pH value of 5.5, and a lanthanum chloride solution having a mass fraction of 3-6% in a weight ratio of 3:4:2.

[0022] S13: The soaked nano-mica powder and the stabilizing adjustment liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 35-45 min. After the ball-milling is completed, the mixture is washed with water and dried to obtain a stabilizing agent adjusted with the nano-mica powder.

[0023] Preferably, the ultrasonic immersion treatment has an ultrasonic immersion power of 400-500 W and an ultrasonic time of 20-30 min.

[0024] Preferably, the preparation method of the stabilization regulating liquid is:

[0025] Stir and mix 4-7 parts of hexagonal boron nitride, 2-5 parts of chitosan solution, and 1-3 parts of glass fiber, then add 2-4 parts of sodium hexametaphosphate aqueous solution and 2-4 parts of yttrium oxide and mix them by ball milling at a speed of 1000-1500r / min for 2h to obtain a stabilizing regulating solution.

[0026] Preferably, the flake diameter of the hexagonal boron nitride is 10-15 µm; the mass fraction of the chitosan solution is 2-5%; and the mass fraction of the sodium hexametaphosphate aqueous solution is 5-8%.

[0027] Preferably, the preparation method of the blending modifier is:

[0028] S101: placing the carbon nanotubes in a sufficient amount of a potassium permanganate solution having a mass fraction of 2-5% and stirring and mixing them thoroughly, then washing and drying to obtain dry carbon nanotubes; placing the dried carbon nanotubes in a proton irradiation box for irradiation treatment, and obtaining a carbon nanotube agent after the irradiation is completed;

[0029] S102: 1-3 parts of silane coupling agent KH550, 2-4 parts of ethanol solvent, 4-7 parts of 5% by mass sodium citrate solution and 1-3 parts of sodium dodecylbenzene sulfonate are fully mixed to obtain a modified solution;

[0030] The carbon nanotube agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a blended modifying agent.

[0031] Preferably, the stirring speed of the stirring modification treatment is 550-750 r / min, and the stirring is for 1 hour; the irradiation power in the proton irradiation box is 400-450 W, and the irradiation is for 5-10 minutes.

[0032] The present invention also provides a method for preparing a weather-resistant metal TPU high and low temperature film, comprising the following steps:

[0033] Step 1: fully blend the raw materials of the TPU film, and then melt extrude the mixture at a temperature of 170°C, and then perform film blowing in a film blowing machine at a temperature of 135°C to obtain a TPU film;

[0034] Step 2, mixing the raw materials in the PU coating patch to form a PU coating patch, coating the PU coating patch on a non-woven fabric base fabric to form a PU bottom layer, a PU middle layer and a PU surface layer, and then compounding the PU bottom layer, the PU middle layer and the PU surface layer to obtain a PU layer;

[0035] Step 3: Bond the upper and lower layers of the PU layer to the TPU layer through a hot melt adhesive layer to obtain a weather-resistant metallic TPU high and low temperature film.

[0036] Compared with the prior art, the present invention has the following beneficial effects:

[0037] 1. The TPU high and low temperature film of the present invention is compounded by a PU layer, a hot melt adhesive layer and a TPU layer. The TPU layer is made of a TPU film. The TPU film uses TPU resin, flame retardant, silane coupling agent KH560, stearic acid, zinc oxide and antioxidant as functional additives. At the same time, a stabilizer and a blending modifier adjusted by mixing nano-mica powder are added as a coordinating agent. The two are coordinated and synergistic, and the product has significant flame retardant and water vapor barrier coordination effects, and the product has obvious weather resistance and high and low temperature stability effects;

[0038] 2. The stabilizer adjusted by mixing with nano-mica powder is prepared by heat-treating the nano-mica powder at 210-230°C for 5-10 minutes, then heating it to 350°C at a rate of 2-5°C / min, keeping it warm for 5 minutes, and finally air-cooling it to room temperature to obtain heat-treated nano-mica powder, optimizing the interlamellar spacing and improving its active performance. At the same time, the immersion liquid is a sodium silicate solution with a mass fraction of 2-5%, a phosphate buffer solution with a pH value of 5.5, and a lanthanum chloride solution with a mass fraction of 3-6% mixed in a weight ratio of 3:4:2; The raw materials in the soaking liquid are coordinated with each other to enhance the coordination effect of the nano mica powder and the stabilizing adjustment liquid. The stabilizing adjustment liquid is ball-milled by mixing hexagonal boron nitride, chitosan solution, glass fiber, sodium hexametaphosphate aqueous solution and yttrium oxide. The structure of the nano mica powder is reinforced by coordinating the hexagonal boron nitride with the glass fiber. At the same time, the chitosan solution, sodium hexametaphosphate aqueous solution and yttrium oxide are further coordinated and synergized. The obtained stabilizing agent adjusted by the blended nano mica powder enhances the flame retardancy and water vapor barrier coordination of the product in the system, as well as the performance stability of the product.

[0039] 3. The blending modifier uses carbon nanotubes treated with potassium permanganate solution to optimize the activity of carbon nanotubes, and then combined with proton irradiation to further enhance the activity of carbon nanotubes. At the same time, the silane coupling agent KH550, ethanol solvent, 5% sodium citrate solution and sodium dodecylbenzene sulfonate in the modified solution are blended and coordinated. Through the synergistic effect between the raw materials, the carbon nanotube system product is improved. The high specific surface area of ​​carbon nanotubes is coordinated and supplemented with the stabilizer adjusted by nano-mica powder, and the performance of the product is further improved.

[0040] 4. The PU coating agent is coated on the non-woven fabric base to make the layer material in the PU layer. The multi-layer composite in the PU layer optimizes the performance of the base product. The weather-resistant metal powder added to the PU coating agent can enhance the weather resistance of the product on the one hand, and on the other hand, it can cooperate with the TPU layer to further enhance the flame retardancy of the product. DETAILED DESCRIPTION

[0041] The following is a clear and complete description of the technical solutions in the embodiments of the present invention in conjunction with specific embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0042] The embodiment of the present invention provides a weather-resistant metal TPU high and low temperature film, comprising a PU layer, a hot melt adhesive layer and a TPU layer; wherein both sides of the PU layer are bonded and compounded by the hot melt adhesive layer and the TPU layer;

[0043] The PU layer also includes a PU bottom layer, a PU middle layer and a PU surface layer, and the PU bottom layer, the PU middle layer and the PU surface layer are arranged in sequence from bottom to top;

[0044] The PU bottom layer, PU middle layer and PU surface layer are all made by coating a PU patch on a non-woven fabric base fabric;

[0045] The PU patch is made of the following raw materials in parts by weight:

[0046] 100-110 parts of polyurethane PU glue, 10-15 parts of butanone solvent, 4-7 parts of weather-resistant metal powder, 2-4 parts of silane coupling agent KH560, and 3-6 parts of curing agent;

[0047] The TPU layer is made of a TPU film, and the TPU film includes the following raw materials in parts by weight:

[0048] 45-55 parts of TPU resin, 8-12 parts of stabilizer adjusted by mixing with nano-mica powder, 4-7 parts of flame retardant, 3-6 parts of blending modifier, 3-5 parts of silane coupling agent KH560, 2-5 parts of stearic acid, 2-5 parts of zinc oxide, and 2-4 parts of antioxidant.

[0049] The weather-resistant metal powder of this embodiment is made of aluminum powder, silicon dioxide, and ferric oxide in a weight ratio of 1:2:1; the curing agent is hexamethylene diisocyanate; the antioxidant is antioxidant 1010; and the flame retardant is magnesium hydroxide.

[0050] The thickness of the TPU layer in this embodiment is 0.3-0.5 mm; the thickness of the PU bottom layer, the PU middle layer and the PU surface layer are all 0.1-0.2 mm; and the thickness of the hot melt adhesive layer is 0.1-0.2 mm.

[0051] The preparation method of the hot melt adhesive layer is as follows:

[0052] 30-35 parts of polyester polyol with a number average molecular weight of 2000, 35-40 parts of toluene diisocyanate, 2 parts of dibutyltin dilaurate, and 4-7 parts of 1,4-butanediol are mixed, and then extruded in a twin-screw extruder at an extrusion temperature of 165° C. After extrusion, the mixture is cooled to obtain a hot melt adhesive layer;

[0053] The polyester polyol is prepared by mixing sebacic acid, terephthalic acid and ethylene glycol in a weight ratio of 1:2:4, then adding isopropyl zirconate of 5% by weight of the sebacic acid, and heating to 140° C. for polycondensation to obtain the polyester polyol.

[0054] The preparation method of the stabilizer mixed with nano-mica powder in this embodiment is as follows:

[0055] S11: heat treating the nano mica powder at 210-230°C for 5-10 min, then heating it to 350°C at a rate of 2-5°C / min, keeping the temperature for 5 min, and finally air cooling it to room temperature to obtain heat-treated nano mica powder;

[0056] S12: immersing the heat-treated nano-mica powder into a sufficient amount of soaking liquid for ultrasonic soaking, filtering and drying after the soaking is completed to obtain soaked nano-mica powder;

[0057] The leaching solution is prepared by mixing a sodium silicate solution having a mass fraction of 2-5%, a phosphate buffer solution having a pH value of 5.5, and a lanthanum chloride solution having a mass fraction of 3-6% in a weight ratio of 3:4:2.

[0058] S13: The soaked nano-mica powder and the stabilizing adjustment liquid are mixed in a weight ratio of 5:3 and ball-milled at a ball-milling speed of 1500 r / min for 35-45 min. After the ball-milling is completed, the mixture is washed with water and dried to obtain a stabilizing agent adjusted with the nano-mica powder.

[0059] The ultrasonic immersion treatment in this embodiment has an ultrasonic immersion power of 400-500W and an ultrasonic time of 20-30min.

[0060] The preparation method of the stabilization regulating liquid of this embodiment is:

[0061] Stir and mix 4-7 parts of hexagonal boron nitride, 2-5 parts of chitosan solution, and 1-3 parts of glass fiber, then add 2-4 parts of sodium hexametaphosphate aqueous solution and 2-4 parts of yttrium oxide and mix them by ball milling at a speed of 1000-1500r / min for 2h to obtain a stabilizing regulating solution.

[0062] The diameter of the hexagonal boron nitride in this embodiment is 10-15 µm; the mass fraction of the chitosan solution is 2-5%; and the mass fraction of the sodium hexametaphosphate aqueous solution is 5-8%.

[0063] The preparation method of the blending modifier of this embodiment is:

[0064] S101: placing the carbon nanotubes in a sufficient amount of a potassium permanganate solution having a mass fraction of 2-5% and stirring and mixing them thoroughly, then washing and drying to obtain dry carbon nanotubes; placing the dried carbon nanotubes in a proton irradiation box for irradiation treatment, and obtaining a carbon nanotube agent after the irradiation is completed;

[0065] S102: 1-3 parts of silane coupling agent KH550, 2-4 parts of ethanol solvent, 4-7 parts of 5% by mass sodium citrate solution and 1-3 parts of sodium dodecylbenzene sulfonate are fully mixed to obtain a modified solution;

[0066] The carbon nanotube agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a blended modifying agent.

[0067] The stirring speed of the stirring modification treatment in this embodiment is 550-750 r / min, and the stirring is for 1 hour; the irradiation power in the proton irradiation box is 400-450 W, and the irradiation is for 5-10 minutes.

[0068] A method for preparing a weather-resistant metallic TPU high and low temperature film of this embodiment comprises the following steps:

[0069] Step 1: fully blend the raw materials of the TPU film, and then melt extrude the mixture at a temperature of 170°C, and then perform film blowing in a film blowing machine at a temperature of 135°C to obtain a TPU film;

[0070] Step 2, mixing the raw materials in the PU coating patch to form a PU coating patch, coating the PU coating patch on a non-woven fabric base fabric to form a PU bottom layer, a PU middle layer and a PU surface layer, and then compounding the PU bottom layer, the PU middle layer and the PU surface layer to obtain a PU layer;

[0071] Step 3: Bond the upper and lower layers of the PU layer to the TPU layer through a hot melt adhesive layer to obtain a weather-resistant metallic TPU high and low temperature film.

[0072] Embodiment 1: A weather-resistant metal TPU high and low temperature film, comprising a PU layer, a hot melt adhesive layer and a TPU layer; wherein both sides of the PU layer are bonded and compounded by the hot melt adhesive layer and the TPU layer;

[0073] The PU layer also includes a PU bottom layer, a PU middle layer and a PU surface layer, and the PU bottom layer, the PU middle layer and the PU surface layer are arranged in sequence from bottom to top;

[0074] The PU bottom layer, PU middle layer and PU surface layer are all made by coating a PU patch on a non-woven fabric base fabric;

[0075] The PU patch is made of the following raw materials in parts by weight:

[0076] 100 parts of polyurethane PU glue, 10 parts of butanone solvent, 4 parts of weather-resistant metal powder, 2 parts of silane coupling agent KH560, and 3 parts of curing agent;

[0077] The TPU layer is made of a TPU film, and the TPU film includes the following raw materials in parts by weight:

[0078] 45 parts of TPU resin, 8 parts of stabilizer adjusted by mixing with nano-mica powder, 4 parts of flame retardant, 3 parts of blending modifier, 3 parts of silane coupling agent KH560, 2 parts of stearic acid, 2 parts of zinc oxide, and 2 parts of antioxidant.

[0079] The weather-resistant metal powder of this embodiment is made of aluminum powder, silicon dioxide, and ferric oxide in a weight ratio of 1:2:1; the curing agent is hexamethylene diisocyanate; the antioxidant is antioxidant 1010; and the flame retardant is magnesium hydroxide.

[0080] The thickness of the TPU layer in this embodiment is 0.3 mm; the thickness of the PU bottom layer, the PU middle layer and the PU surface layer are all 0.1 mm; and the thickness of the hot melt adhesive layer is 0.1 mm.

[0081] The preparation method of the hot melt adhesive layer is as follows:

[0082] 30 parts of polyester polyol with a number average molecular weight of 2000, 35 parts of toluene diisocyanate, 2 parts of dibutyltin dilaurate, and 4 parts of 1,4-butanediol were mixed and then extruded in a twin-screw extruder at an extrusion temperature of 165° C. After extrusion, the mixture was cooled to obtain a hot melt adhesive layer;

[0083] The polyester polyol is prepared by mixing sebacic acid, terephthalic acid and ethylene glycol in a weight ratio of 1:2:4, then adding isopropyl zirconate of 5% by weight of the sebacic acid, and heating to 140° C. for polycondensation to obtain the polyester polyol.

[0084] The preparation method of the stabilizer mixed with nano-mica powder in this embodiment is as follows:

[0085] S11: heat-treating the nano-mica powder at 210° C. for 5 min, then heating the nano-mica powder to 350° C. at a rate of 2° C. / min, keeping the temperature for 5 min, and finally air-cooling the nano-mica powder to obtain heat-treated nano-mica powder;

[0086] S12: immersing the heat-treated nano-mica powder into a sufficient amount of soaking liquid for ultrasonic soaking, filtering and drying after the soaking is completed to obtain soaked nano-mica powder;

[0087] The leaching solution is prepared by mixing 2% sodium silicate solution by weight, phosphate buffer solution with a pH value of 5.5, and 3% lanthanum chloride solution by weight in a ratio of 3:4:2.

[0088] S13: The soaked nano-mica powder and the stabilizing adjustment liquid are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 35 minutes. After the ball-milling is completed, the mixture is washed with water and dried to obtain a stabilizing agent adjusted with the nano-mica powder.

[0089] The ultrasonic immersion treatment in this embodiment has an ultrasonic immersion power of 400 W and an ultrasonic time of 20 min.

[0090] The preparation method of the stabilization regulating liquid of this embodiment is:

[0091] Stir and mix 4 parts of hexagonal boron nitride, 2 parts of chitosan solution and 1 part of glass fiber, then add 2 parts of sodium hexametaphosphate aqueous solution and 2 parts of yttrium oxide and mix them by ball milling at a speed of 1000 r / min for 2 hours to obtain a stabilizing regulating solution.

[0092] The diameter of the hexagonal boron nitride in this embodiment is 10 μm; the mass fraction of the chitosan solution is 2%; and the mass fraction of the sodium hexametaphosphate aqueous solution is 5%.

[0093] The preparation method of the blending modifier of this embodiment is:

[0094] S101: placing the carbon nanotubes in a sufficient amount of a 2% by mass potassium permanganate solution and stirring and mixing them thoroughly, then washing and drying to obtain dry carbon nanotubes; placing the dried carbon nanotubes in a proton irradiation box for irradiation treatment, and obtaining a carbon nanotube agent after the irradiation is completed;

[0095] S102: fully mixing 1 part of silane coupling agent KH550, 2 parts of ethanol solvent, 4 parts of 5% by mass sodium citrate solution and 1 part of sodium dodecylbenzene sulfonate to obtain a modified solution;

[0096] The carbon nanotube agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a blended modifying agent.

[0097] The stirring speed of the stirring modification treatment in this embodiment is 550 r / min, and the stirring is for 1 hour; the irradiation power in the proton irradiation box is 400 W, and the irradiation is for 5 minutes.

[0098] A method for preparing a weather-resistant metallic TPU high and low temperature film of this embodiment comprises the following steps:

[0099] Step 1: fully blend the raw materials of the TPU film, and then melt extrude the mixture at a temperature of 170°C, and then perform film blowing in a film blowing machine at a temperature of 135°C to obtain a TPU film;

[0100] Step 2, mixing the raw materials in the PU coating patch to form a PU coating patch, coating the PU coating patch on a non-woven fabric base fabric to form a PU bottom layer, a PU middle layer and a PU surface layer, and then compounding the PU bottom layer, the PU middle layer and the PU surface layer to obtain a PU layer;

[0101] Step 3: Bond the upper and lower layers of the PU layer to the TPU layer through a hot melt adhesive layer to obtain a weather-resistant metallic TPU high and low temperature film.

[0102] Embodiment 2: A weather-resistant metal TPU high and low temperature film, comprising a PU layer, a hot melt adhesive layer and a TPU layer; wherein both sides of the PU layer are bonded and compounded with the TPU layer by the hot melt adhesive layer;

[0103] The PU layer also includes a PU bottom layer, a PU middle layer and a PU surface layer, and the PU bottom layer, the PU middle layer and the PU surface layer are arranged in sequence from bottom to top;

[0104] The PU bottom layer, PU middle layer and PU surface layer are all made by coating a PU patch on a non-woven fabric base fabric;

[0105] The PU patch is made of the following raw materials in parts by weight:

[0106] 110 parts of polyurethane PU glue, 15 parts of butanone solvent, 7 parts of weather-resistant metal powder, 4 parts of silane coupling agent KH560, and 6 parts of curing agent;

[0107] The TPU layer is made of a TPU film, and the TPU film includes the following raw materials in parts by weight:

[0108] 55 parts of TPU resin, 12 parts of stabilizer adjusted by mixing with nano-mica powder, 7 parts of flame retardant, 6 parts of blending modifier, 5 parts of silane coupling agent KH560, 5 parts of stearic acid, 5 parts of zinc oxide, and 4 parts of antioxidant.

[0109] The weather-resistant metal powder of this embodiment is made of aluminum powder, silicon dioxide, and ferric oxide in a weight ratio of 1:2:1; the curing agent is hexamethylene diisocyanate; the antioxidant is antioxidant 1010; and the flame retardant is magnesium hydroxide.

[0110] The thickness of the TPU layer in this embodiment is 0.5 mm; the thickness of the PU bottom layer, the PU middle layer and the PU surface layer are all 0.2 mm; and the thickness of the hot melt adhesive layer is 0.2 mm.

[0111] The preparation method of the hot melt adhesive layer is as follows:

[0112] 35 parts of polyester polyol with a number average molecular weight of 2000, 40 parts of toluene diisocyanate, 2 parts of dibutyltin dilaurate, and 7 parts of 1,4-butanediol were mixed and then extruded in a twin-screw extruder at an extrusion temperature of 165° C. After extrusion, the mixture was cooled to obtain a hot melt adhesive layer;

[0113] The polyester polyol is prepared by mixing sebacic acid, terephthalic acid and ethylene glycol in a weight ratio of 1:2:4, then adding isopropyl zirconate of 5% by weight of the sebacic acid, and heating to 140° C. for polycondensation to obtain the polyester polyol.

[0114] The preparation method of the stabilizer mixed with nano-mica powder in this embodiment is as follows:

[0115] S11: heat treating the nano mica powder at 230°C for 10 min, then heating the nano mica powder to 350°C at a rate of 5°C / min, keeping the temperature for 5 min, and finally cooling the nano mica powder to room temperature, thereby obtaining heat treated nano mica powder;

[0116] S12: immersing the heat-treated nano-mica powder into a sufficient amount of soaking liquid for ultrasonic soaking, filtering and drying after the soaking is completed to obtain soaked nano-mica powder;

[0117] The leaching solution is prepared by mixing 5% sodium silicate solution by weight, phosphate buffer solution with a pH value of 5.5, and 6% lanthanum chloride solution by weight in a ratio of 3:4:2.

[0118] S13: The soaked nano-mica powder and the stabilizing adjustment liquid are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 45 minutes. After the ball-milling is completed, the mixture is washed with water and dried to obtain a stabilizing agent adjusted with the nano-mica powder.

[0119] The ultrasonic immersion treatment in this embodiment has an ultrasonic immersion power of 500 W and an ultrasonic time of 30 min.

[0120] The preparation method of the stabilization regulating liquid of this embodiment is:

[0121] 7 parts of hexagonal boron nitride, 5 parts of chitosan solution and 3 parts of glass fiber are stirred and mixed first, and then 4 parts of sodium hexametaphosphate aqueous solution and 4 parts of yttrium oxide are added and mixed and ball-milled at a ball-milling speed of 1500 r / min for 2 hours to obtain a stabilizing regulating solution.

[0122] The diameter of the hexagonal boron nitride in this embodiment is 15 µm; the mass fraction of the chitosan solution is 5%; and the mass fraction of the sodium hexametaphosphate aqueous solution is 8%.

[0123] The preparation method of the blending modifier of this embodiment is:

[0124] S101: placing the carbon nanotubes in a sufficient amount of a 5% by mass potassium permanganate solution and stirring and mixing them thoroughly, then washing and drying to obtain dried carbon nanotubes; placing the dried carbon nanotubes in a proton irradiation box for irradiation treatment, and obtaining a carbon nanotube agent after the irradiation is completed;

[0125] S102: 3 parts of silane coupling agent KH550, 4 parts of ethanol solvent, 7 parts of 5% by mass sodium citrate solution and 3 parts of sodium dodecylbenzene sulfonate are fully mixed to obtain a modified solution;

[0126] The carbon nanotube agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a blended modifying agent.

[0127] The stirring speed of the stirring modification treatment in this embodiment is 750 r / min, and the stirring is for 1 hour; the irradiation power in the proton irradiation box is 450 W, and the irradiation is for 10 minutes.

[0128] A method for preparing a weather-resistant metallic TPU high and low temperature film of this embodiment comprises the following steps:

[0129] Step 1: fully blend the raw materials of the TPU film, and then melt extrude the mixture at a temperature of 170°C, and then perform film blowing in a film blowing machine at a temperature of 135°C to obtain a TPU film;

[0130] Step 2, mixing the raw materials in the PU coating patch to form a PU coating patch, coating the PU coating patch on a non-woven fabric base fabric to form a PU bottom layer, a PU middle layer and a PU surface layer, and then compounding the PU bottom layer, the PU middle layer and the PU surface layer to obtain a PU layer;

[0131] Step 3: Bond the upper and lower layers of the PU layer to the TPU layer through a hot melt adhesive layer to obtain a weather-resistant metallic TPU high and low temperature film.

[0132] Embodiment 3: A weather-resistant metal TPU high and low temperature film, comprising a PU layer, a hot melt adhesive layer and a TPU layer; wherein both sides of the PU layer are bonded and compounded by the hot melt adhesive layer and the TPU layer;

[0133] The PU layer also includes a PU bottom layer, a PU middle layer and a PU surface layer, and the PU bottom layer, the PU middle layer and the PU surface layer are arranged in sequence from bottom to top;

[0134] The PU bottom layer, PU middle layer and PU surface layer are all made by coating a PU patch on a non-woven fabric base fabric;

[0135] The PU patch is made of the following raw materials in parts by weight:

[0136] 105 parts of polyurethane PU glue, 12.5 parts of butanone solvent, 5.5 parts of weather-resistant metal powder, 3 parts of silane coupling agent KH560, and 4.5 parts of curing agent;

[0137] The TPU layer is made of a TPU film, and the TPU film includes the following raw materials in parts by weight:

[0138] 50 parts of TPU resin, 10 parts of stabilizer adjusted by mixing with nano-mica powder, 5.5 parts of flame retardant, 4.5 parts of blending modifier, 4 parts of silane coupling agent KH560, 3.5 parts of stearic acid, 3.5 parts of zinc oxide, and 3 parts of antioxidant.

[0139] The weather-resistant metal powder of this embodiment is made of aluminum powder, silicon dioxide, and ferric oxide in a weight ratio of 1:2:1; the curing agent is hexamethylene diisocyanate; the antioxidant is antioxidant 1010; and the flame retardant is magnesium hydroxide.

[0140] The thickness of the TPU layer in this embodiment is 0.4 mm; the thickness of the PU bottom layer, the PU middle layer and the PU surface layer are all 0.15 mm; and the thickness of the hot melt adhesive layer is 0.15 mm.

[0141] The preparation method of the hot melt adhesive layer is as follows:

[0142] 32.5 parts of polyester polyol with a number average molecular weight of 2000, 37.5 parts of toluene diisocyanate, 2 parts of dibutyltin dilaurate, and 5.5 parts of 1,4-butanediol were mixed and then extruded in a twin-screw extruder at an extrusion temperature of 165° C. After extrusion, the mixture was cooled to obtain a hot melt adhesive layer;

[0143] The polyester polyol is prepared by mixing sebacic acid, terephthalic acid and ethylene glycol in a weight ratio of 1:2:4, then adding isopropyl zirconate of 5% by weight of the sebacic acid, and heating to 140° C. for polycondensation to obtain the polyester polyol.

[0144] The preparation method of the stabilizer mixed with nano-mica powder in this embodiment is as follows:

[0145] S11: heat treating the nano mica powder at 220°C for 7.5 minutes, then heating the nano mica powder to 350°C at a rate of 3.5°C / min, keeping the temperature for 5 minutes, and finally air cooling the nano mica powder to obtain heat treated nano mica powder;

[0146] S12: immersing the heat-treated nano-mica powder into a sufficient amount of soaking liquid for ultrasonic soaking, filtering and drying after the soaking is completed to obtain soaked nano-mica powder;

[0147] The leaching solution is prepared by mixing 3.5% sodium silicate solution, phosphate buffer solution with a pH value of 5.5, and 4.5% lanthanum chloride solution in a weight ratio of 3:4:2.

[0148] S13: The soaked nano-mica powder and the stabilizing adjustment liquid are mixed in a weight ratio of 5:3 and ball-milled at a speed of 1500 r / min for 40 minutes. After the ball-milling is completed, the mixture is washed with water and dried to obtain a stabilizing agent adjusted with the nano-mica powder.

[0149] The ultrasonic immersion treatment in this embodiment has an ultrasonic immersion power of 450 W and an ultrasonic time of 25 min.

[0150] The preparation method of the stabilization regulating liquid of this embodiment is:

[0151] 5.5 parts of hexagonal boron nitride, 3.5 parts of chitosan solution and 2 parts of glass fiber are stirred and mixed first, and then 3 parts of sodium hexametaphosphate aqueous solution and 3 parts of yttrium oxide are added and mixed and ball-milled at a ball-milling speed of 1250 r / min for 2 hours to obtain a stabilizing regulating solution.

[0152] The diameter of the hexagonal boron nitride in this embodiment is 12.5 µm; the mass fraction of the chitosan solution is 3.5%; and the mass fraction of the sodium hexametaphosphate aqueous solution is 6.5%.

[0153] The preparation method of the blending modifier of this embodiment is:

[0154] S101: placing the carbon nanotubes in a sufficient amount of a 3.5% by mass potassium permanganate solution and stirring and mixing them thoroughly, then washing and drying to obtain dry carbon nanotubes; placing the dried carbon nanotubes in a proton irradiation box for irradiation treatment, and obtaining a carbon nanotube agent after the irradiation is completed;

[0155] S102: 2 parts of silane coupling agent KH550, 3 parts of ethanol solvent, 5.5 parts of 5% by mass sodium citrate solution and 12 parts of sodium dodecylbenzene sulfonate are fully mixed to obtain a modified solution;

[0156] The carbon nanotube agent and the modifying liquid are stirred and modified in a weight ratio of 2:5. After the stirring is completed, the mixture is washed with water and dried to obtain a blended modifying agent.

[0157] The stirring speed of the stirring modification treatment in this embodiment is 600 r / min, and the stirring is for 1 hour; the irradiation power in the proton irradiation box is 420 W, and the irradiation is for 7.5 minutes.

[0158] A method for preparing a weather-resistant metallic TPU high and low temperature film of this embodiment comprises the following steps:

[0159] Step 1: fully blend the raw materials of the TPU film, and then melt extrude the mixture at a temperature of 170°C, and then perform film blowing in a film blowing machine at a temperature of 135°C to obtain a TPU film;

[0160] Step 2, mixing the raw materials in the PU coating patch to form a PU coating patch, coating the PU coating patch on a non-woven fabric base fabric to form a PU bottom layer, a PU middle layer and a PU surface layer, and then compounding the PU bottom layer, the PU middle layer and the PU surface layer to obtain a PU layer;

[0161] Step 3: Bond the upper and lower layers of the PU layer to the TPU layer through a hot melt adhesive layer to obtain a weather-resistant metallic TPU high and low temperature film.

[0162] Comparative Example 1:

[0163] The difference from Example 3 is that the coating stabilizer adjusted by mixing with nano-mica powder is not added.

[0164] Comparative Example 2:

[0165] The difference from Example 3 is that the S11 step is not used in the preparation of the stabilizer adjusted by mixing with nano-mica powder.

[0166] Comparative Example 3:

[0167] The difference from Example 3 is that no soaking liquid treatment is used in the preparation of the stabilizer adjusted by mixing with nano-mica powder.

[0168] Comparative Example 4:

[0169] The difference from Example 3 is that no lanthanum chloride solution and sodium silicate solution are added to the leaching solution.

[0170] Comparative Example 5:

[0171] The difference from Example 3 is that no stabilizing regulating liquid treatment is used.

[0172] Comparative Example 6:

[0173] The difference from Example 3 is that no blending modifier is added.

[0174] Comparative Example 7:

[0175] The difference from Example 3 is that no modifying liquid treatment is used in the preparation of the modifier.

[0176] Comparative Example 8:

[0177] The difference from Example 3 is that no silane coupling agent KH550 and sodium dodecylbenzene sulfonate are added to the modified liquid.

[0178] The product performance of Examples 1-3 and Comparative Examples 1-8 was tested routinely, and the UV intensity was 400uW / cm 2 , ozone concentration 20ppm, temperature 35℃ weathering and aging conditions for 24h, then placed at 55℃ for 24h, transferred to -5℃ for 24h. The above is one cycle. The product is cycled 5 times to test its weather resistance, high and low temperature resistance and take the average value. The performance measurement results are shown in Table 1.

[0179] Table 1: Product performance test results of Examples 1-3 and Comparative Examples 1-8:

[0180]

[0181] It can be concluded from Table 1 that the product of Example 3 of the present invention has excellent flame retardancy and barrier properties under normal conditions, and the two can be improved in a coordinated manner. At the same time, the product has significant performance stability under weather resistance and high and low temperature resistance conditions;

[0182] From Comparative Examples 1-8 and Example 3, it can be seen that the product does not add any of the stabilizer adjusted by mixing with nano-mica powder and the blending modifier, and the performance of the product deteriorates most significantly. The synergistic effect of the two is used, and the product performance effect is most significant.

[0183] The performance of the product showed a trend of deterioration to varying degrees when the S11 step was not used in the preparation of the stabilizer adjusted by nano-mica powder, the soaking liquid was not used in the preparation of the stabilizer adjusted by nano-mica powder, the lanthanum chloride solution and the sodium silicate solution were not added to the soaking liquid, and the stabilization adjusting liquid was not used. The performance of the product deteriorated significantly when the stabilization adjusting liquid was not used. The stabilizer adjusted by nano-mica powder prepared by the soaking liquid obtained by the method of the present invention and the stabilization adjusting liquid of the present invention had the most significant product performance effect. Other methods were not as obvious as the effect of the present invention.

[0184] The performance of the product also showed a trend of deterioration when the modifying liquid was not used in the blending modifier and the silane coupling agent KH550 and sodium dodecylbenzene sulfonate were not added to the modifying liquid. The performance of the blending modifiers obtained by using different modifying liquids showed a trend of deterioration.

[0185] Based on the fact that the stabilizing regulating fluid has a significant impact on the performance of the product, further research is conducted on this.

[0186] Experimental Example 1:

[0187] The only difference from Example 3 is that hexagonal boron nitride is not added to the stabilization adjustment solution.

[0188] Experimental Example 2:

[0189] The only difference from Example 3 is that no chitosan solution is added to the stabilization regulating solution.

[0190] Experimental Example 3:

[0191] The only difference from Example 3 is that yttrium oxide is not added to the stabilization adjustment solution.

[0192] Experimental Example 4:

[0193] The only difference from Example 3 is that no glass fiber is added to the stabilization adjustment liquid.

[0194] Experimental Example 5:

[0195] The only difference from Example 3 is that no sodium hexametaphosphate aqueous solution is added to the stabilization adjustment solution.

[0196] The product performance of Experimental Examples 1-5 was tested routinely, and the UV intensity was 400uW / cm 2 , ozone concentration 20ppm, temperature 35℃ weathering and aging conditions for 24h, then placed at 55℃ for 24h, transferred to -5℃ for 24h. The above is one cycle. The product is cycled 5 times to test its weather resistance, high and low temperature resistance and take the average value. The performance measurement results are shown in Table 2.

[0197] Table 2: Product performance test results of Experimental Examples 1-5:

[0198]

[0199] As can be seen from Table 2, when hexagonal boron nitride is not added to the stabilization regulating liquid, the performance of the product has the greatest impact on the stabilization regulating liquid, followed by the absence of glass fiber. At the same time, when chitosan solution, yttrium oxide and sodium hexametaphosphate aqueous solution are not added to the stabilization regulating liquid, the performance of the product tends to deteriorate. The raw materials in the composition of the stabilization regulating liquid are indispensable, and the use of other methods to replace them in the product composition tends to deteriorate to varying degrees. Only when the stabilization regulating liquid of the present invention is used, the product performance effect is most significant.

[0200] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0201] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A weather-resistant metal TPU high and low temperature film, characterized in that: It includes a PU layer, a hot melt adhesive layer and a TPU layer; wherein both sides of the PU layer are bonded and compounded by the hot melt adhesive layer and the TPU layer; The PU layer also includes a PU bottom layer, a PU middle layer and a PU surface layer, and the PU bottom layer, the PU middle layer and the PU surface layer are arranged in sequence from bottom to top; The PU bottom layer, PU middle layer and PU surface layer are all made by coating a PU patch on a non-woven fabric base fabric; The PU patch is made of the following raw materials in parts by weight: 100-110 parts of polyurethane PU glue, 10-15 parts of butanone solvent, 4-7 parts of weather-resistant metal powder, 2-4 parts of silane coupling agent KH560, and 3-6 parts of curing agent; The TPU layer is made of a TPU film, and the TPU film includes the following raw materials in parts by weight: 45-55 parts of TPU resin, 8-12 parts of stabilizer adjusted by mixing with nano-mica powder, 4-7 parts of flame retardant, 3-6 parts of blending modifier, 3-5 parts of silane coupling agent KH560, 2-5 parts of stearic acid, 2-5 parts of zinc oxide, and 2-4 parts of antioxidant; The preparation method of the stabilizer mixed with nano-mica powder is as follows: S11: heat treating the nano mica powder at 210-230°C for 5-10 min, then heating it to 350°C at a rate of 2-5°C / min, keeping the temperature for 5 min, and finally air cooling it to room temperature to obtain heat-treated nano mica powder; S12: immersing the heat-treated nano-mica powder into a sufficient amount of soaking liquid for ultrasonic soaking, filtering and drying after the soaking is completed to obtain soaked nano-mica powder; The leaching solution is prepared by mixing a sodium silicate solution having a mass fraction of 2-5%, a phosphate buffer solution having a pH value of 5.5, and a lanthanum chloride solution having a mass fraction of 3-6% in a weight ratio of 3:4:

2. S13: mixing the soaked nano-mica powder and the stabilizing agent in a weight ratio of 5:3, and ball milling the mixture at a speed of 1500 r / min for 35-45 min. After the ball milling is completed, washing and drying are performed to obtain a stabilizing agent mixed with nano-mica powder; The preparation method of the stabilization regulating liquid is as follows: 4-7 parts of hexagonal boron nitride, 2-5 parts of chitosan solution, and 1-3 parts of glass fiber are stirred and mixed, and then 2-4 parts of sodium hexametaphosphate aqueous solution and 2-4 parts of yttrium oxide are added and mixed and ball-milled at a ball-milling speed of 1000-1500 r / min for 2 hours to obtain a stabilizing regulating solution; The preparation method of the blending modifier is: S101: placing the carbon nanotubes in a sufficient amount of a potassium permanganate solution having a mass fraction of 2-5% and stirring and mixing them thoroughly, then washing and drying to obtain dry carbon nanotubes; placing the dried carbon nanotubes in a proton irradiation box for irradiation treatment, and obtaining a carbon nanotube agent after the irradiation is completed; S102: 1-3 parts of silane coupling agent KH550, 2-4 parts of ethanol solvent, 4-7 parts of 5% by mass sodium citrate solution and 1-3 parts of sodium dodecylbenzene sulfonate are fully mixed to obtain a modified solution; The carbon nanotube agent and the modifying liquid are stirred and modified in a weight ratio of 2:

5. After the stirring is completed, the mixture is washed with water and dried to obtain a blended modifying agent.

2. A weather-resistant metal TPU high and low temperature film according to claim 1, characterized in that: The weather-resistant metal powder is made of aluminum powder, silicon dioxide and ferric oxide in a weight ratio of 1:2:1; the curing agent is hexamethylene diisocyanate; the antioxidant is antioxidant 1010; and the flame retardant is magnesium hydroxide.

3. The weather-resistant metal TPU high and low temperature film according to claim 1, characterized in that: The thickness of the TPU layer is 0.3-0.5 mm; the thickness of the PU bottom layer, the PU middle layer and the PU surface layer are all 0.1-0.2 mm; the thickness of the hot melt adhesive layer is 0.1-0.2 mm; The preparation method of the hot melt adhesive layer is as follows: 30-35 parts of polyester polyol with a number average molecular weight of 2000, 35-40 parts of toluene diisocyanate, 2 parts of dibutyltin dilaurate, and 4-7 parts of 1,4-butanediol are mixed, and then extruded in a twin-screw extruder at an extrusion temperature of 165° C. After extrusion, the mixture is cooled to obtain a hot melt adhesive layer; The polyester polyol is prepared by mixing sebacic acid, terephthalic acid and ethylene glycol in a weight ratio of 1:2:4, then adding isopropyl zirconate of 5% by weight of the sebacic acid, and heating to 140° C. for polycondensation to obtain the polyester polyol.

4. The weather-resistant metallic TPU high and low temperature film according to claim 1, characterized in that: The ultrasonic immersion treatment has an ultrasonic immersion power of 400-500W and an ultrasonic time of 20-30min.

5. The weather-resistant metallic TPU high and low temperature film according to claim 1, characterized in that: The flake diameter of the hexagonal boron nitride is 10-15 µm; the mass fraction of the chitosan solution is 2-5%; and the mass fraction of the sodium hexametaphosphate aqueous solution is 5-8%.

6. The weather-resistant metal TPU high and low temperature film according to claim 1, characterized in that: The stirring speed of the stirring modification treatment is 550-750r / min, and the stirring is for 1 hour; the irradiation power in the proton irradiation box is 400-450W, and the irradiation is for 5-10 minutes.

7. A method for preparing a weather-resistant metal TPU high and low temperature film, used for preparing the weather-resistant metal TPU high and low temperature film according to any one of claims 1 to 6, characterized in that: The following steps are involved: Step 1: fully blend the raw materials of the TPU film, and then melt extrude the mixture at a temperature of 170°C, and then perform film blowing in a film blowing machine at a temperature of 135°C to obtain a TPU film; Step 2, mixing the raw materials in the PU coating patch to form a PU coating patch, coating the PU coating patch on a non-woven fabric base to form a PU bottom layer, a PU middle layer and a PU surface layer, and then compounding the PU bottom layer, the PU middle layer and the PU surface layer to obtain a PU layer; Step 3: Bond the upper and lower layers of the PU layer to the TPU layer through a hot melt adhesive layer to obtain a weather-resistant metallic TPU high and low temperature film.

Citation Information

Patent Citations

  • High-scratch-resistance TPU film and preparation method thereof

    CN110903633A

  • High-temperature-resistant film

    CN115742518A

  • Heat-resistant stable TPU film and preparation method thereof

    CN117186623A